Effect of commercial crossing of Šumavska sheep with selected meat breeds on carcass characteristics of lambs - Koutná, Svatava; Kuchtík, Jan; Šťastník, Ondřej; Konečná, Leona (Animal Welfare, Etológia és Tartástechnológia (AWETH), 2017)
Evaluation of the effect of commercial crossing of Šumavska sheep (S) with selected meat breeds (Suffolk (SF) and Texel (T) on basic carcass and non-carcass traits of lambs was carried out on an organic farm in Proseč in the Pardubice region. Four different genotypes were included in the experiment: SF x S (n = 9), S (n = 11), SF x (T 75 S 25) (n = 12) and S x (T 75 S 25) (n = 14). All lambs in the study were males. The highest daily gain (0.166 kg/day), carcass yield (43.96 %) and proportion of muscle and fat in the left leg (79.25 %) were found in crossbreds SF x (T 75 S 25) while in this group was the highest proportion of meat breeds. In contrast, in purebred lambs of Šumavská sheep the lowest daily gain (0.122 kg/day), carcass yield (37.71 %) and proportion of muscle and fat in left leg (74.47 %) were found. The best conformation score and the lowest fatness score (2.22) were found in crossbreds SF x S. On the other hand in purebred lambs of Šumavska sheep the worst conformation score (4.91) was found. However in this group relatively very favorable fatness score (2.27) was also found. The results of the experiment indicate that use of commercial crossing of ewes of Šumavská breed with rams of meat breeds had a positive effect on the most of the monitored carcass traits.